Developing Recombinant Antibodies by Phage Display Against Infectious Diseases and Toxins for Diagnostics and Therapy - Roth, Kristian Daniel Ralph; Wenzel, Esther Veronika; Ruschig, Maximilian; Steinke, Stephan; Langreder, Nora; Heine, Philip Alexander; Schneider, Kai-Thomas; Ballmann, Rico; Fühner, Viola; Kuhn, Philipp; Schirrmann, Thomas; Frenzel, André; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Antibodies are essential molecules for diagnosis and treatment of diseases caused by pathogens and their toxins. Despite antibodies were integrated in our medical repertoire against infectious diseases more than hundred years ago to treat tetanus and diphtheria, most recently developed therapeutic antibodies target cancer or autoimmune diseases. The COVID-19 pandemic was a reminder about the importance of antibodies for therapy against infectious diseases. While, monoclonal antibodies could be generated by hybridoma technology since the 70ies of the former century, nowadays antibody phage display, among other display technologies, is robustly established to discover new human monoclonal antibodies. This in vitro technology circumvents some of the limitations of the immune system and confers the potential for generating antibodies against any conceivable molecule of sufficient size. Phage display technology allows to generate human antibodies from naïve antibody gene libraries when either patients are not available or immunization is not ethically feasible. On the other hand, if convalescent patients or immunized/infected animals are available, it is possible to construct immune phage display libraries to select in vivo affinity-matured antibodies. Because the phage-packaged DNA sequence encoding the antibodies is always directly available, the antibodies can be rapidly further engineered according to the requirements of the final application. In this review, we give an overview of phage display derived recombinant antibodies against bacterial, viral and eukaryotic pathogens as well as microbial toxins for diagnostics and therapy.